The Influence of Skill Level, Work Discipline and Work Environment on the Work Productivity of Tire Building Employees PT. Ban Indonesia - Wahyudi, Dendi; Rafi, Affan; Farhan, Aan; Wiyatno, Tri Ngudi (Formosa Journal of Sustainable Research, 2024)
This research is motivated by the rapid economic growth in Indonesia. To develop business in the modern era, companies must be able to compete in the business world. This research aims to understand how skills, work discipline and work environment influence employee productivity. The population of this study are employees of a Korean company located in Bekasi Regency and producing bicycle tires, with a population of 2,700 employees in 2022. However, this research focuses on the group B tire building section which consists of 82 employees in 2022. Research reveals that skills, work environment and work discipline provide a positive influence and significant increase in employee productivity. In other words, improving skills, work discipline and a conducive work environment can increase productivity in the company